Analysis of Teacher Discipline and Student Learning Attitudes in Class XI Biology Subjects at SMA District of Kampung Rakyat - Hasibuan, Seri Amalia; Harahap, Hasmi Syahputra (Budapest International Research and Critics University, 2022)
This study aims to analyze teacher discipline and student learning attitudes in biology class XI in SMA in the village of the people. The subjects of this research are teachers and students. The population in this study were 3 biology teachers and 114 students. The research instrument used in the form of a questionnaire evaluation of students' attitudes and abilities in understanding biology and interviews with biology teachers. The research method used is descriptive qualitative. Data collection techniques with the method of observation, questionnaires and interviews. Based on the results of the study the authors concluded that the learning process of biology in each school was carried out with limited face-to-face. In each lesson schedule, teachers always come on time and carry out their duties and responsibilities as teachers in biology. Students' learning attitudes towards biology subjects are classified as standard, but when learning uses practical demonstrations, students' learning attitudes are classified as increasing. Based on the results of interviews that researchers obtained, there were several obstacles in the student learning process including the lack of full face-to-face learning and the lack of facilities and infrastructure for learning biology which caused students' interest in learning to vary in biology.